Hubungan Kemampuan Sosialisasi dengan Keterbukaan Diri Siswa Kelas VIII - Saputri, Lintang Dewi; Triyanto, Endang; Swasti, Keksi Girindra (Jurusan Keperawatan FIKES UNSOED, 2012)
The socialization ability is a personï¿½s ability when interacting with others people the community. In times of social change, students seeking self-identity. In search of identity is they must have the socialization ability to open their self. The purpose of this reasearch is to identify relationship the ability with self disclosure in students class VIII at SMP Giripuro Sumpiuh. This was quantitative non-experimental method with crossectional approach reasearch. The population was 121 student class VIII at SMP Giripuro Sumpiuh, then the responden is 55 students were selected as sample choosen by purposive sampling. The data analysis used Chi square. Chi square test show that 39 students (70.9%) have good socialization ability, 28 students are good socialization skills but keterbukaan diri enough. While students who have less social skills were 7 students (12.7%), two student self disclosure is high. The results of statistical analysis Chi square test obtained that there is a significantï¿½s relationship between the ability to socialize with studentï¿½s self disclosure. There was significant relation between the socialization ability and self disclosure in VIII class students at SMP Giripuro Sumpiuh.